Ninjinyoeito Has a Protective Effect on the Auditory Nerve and Suppresses the Progression of Age-Related Hearing Loss in Mice - Kawashima, Takanori; Harai, Kenji; Fujita, Nina; Takahashi, Ryuji (Frontiers in Nutrition, 2020)
Currently, there are limited reports available regarding the treatment and prevention of progressive age-related hearing loss. This is because age-related hearing loss is not a critical disease with direct fatalities and has several well-established countermeasures such as hearing aids and cochlear implants. This study evaluated the efficacy of Ninjinyoeito (NYT) in the treatment of age-related hearing loss. C57BL/6J mice were divided into three groups: baseline group, untreated group, and NYT-treated group, with the latter receiving NYT treatment for 2 months. The mice were fed with NYT extract mixed with 4% mouse normal chow. Hearing loss was confirmed by a reduction in intact cell density of the auditory nerve from the age of 5–7 months. The suppression of hearing loss with aging and decrease in the intact cell density of the auditory nerve were significant in mice fed with NYT for 2 months. NYT has been reported to improve blood flow and enhance mitochondrial activity and may exert its protective effects on spiral neurons through these mechanisms. There was no decrease in the size of the stria vascularis from the age of 5–7 months in C57BL/6J mice. The present model failed to reveal the effect of NYT on atrophy of the stria vascularis of the cochlear duct. In conclusion, NYT appears to have a protective effect on the auditory nerve and suppress the progression of age-related hearing loss by reducing age-related auditory nerve degeneration.